A generalist grasshopper species (Melanoplus femurrubrum) is adapted to variable environments along a latitudinal gradient - Parsons, Sheena Marie Aiko (Kansas State University, 2011)
Temperature and food quality vary across broad latitudinal gradients, greatly affecting performance by insect herbivores. The contribution of each varies latitudinally so that geographically distinct populations are challenged by differences in nutritional needs and energetic demands. While there has been extensive work studying diet selectivity and nutritional ecology of insect herbivores, few studies have focused on how insect herbivores adapt across such vast environmental gradients. The generalist-feeding grasshopper, Melanoplus femurrubrum (DeGreer), has a broad geographic range that extends across much of North America, making this species ideal for comparative investigations of intrinsic performance responses to extensive but predictable patterns of environmental variation. I compared responses by six populations collected from populations located from Texas to North Dakota (USA) using a common garden experimental design to investigate clinal responses in grasshopper performance. I examined responses in: (1) body size, (2) thermoregulation and adaptive coloration, (3) developmental and growth rates, (4) metabolic rates, (5) total consumption and rates, (6) diet ratio selection, and (7) digestive processing efficiencies across the latitudinal gradient. Grasshopper body size followed the Converse Bergmann’s Rule with decreasing body size as latitude increased. Temperature influenced all other responses, but responses to diet were not always significant or directional. Latitudinal trends for development and growth rates were observed but mass-specific metabolic rates were similar for all populations. Total consumption was body size dependent but independent of diet type. Mass-specific consumption varied but no single directional trend was detected. There was a shift in carbohydrate-biased diet preference at low latitude toward protein-biased diet ratios at higher latitudes, suggesting adaptations to different energetic demands by these populations. However, post-ingestive (digestive) efficiencies demonstrated variable responses with northern populations observing highest efficiencies for some indices but not all. Overall, this research documents phenotypic plasticity to environmental variability to some degree for digestive efficiencies, but ecotypic responses in body size and diet preference among M. femurrubrum populations were observed.
Keywords: Melanoplus femurrubrum; Latitudinal gradient; Body size; Nutritional ecology; Temperature; Performance; Biology, Animal Physiology (0433); Ecology (0329); Entomology (0353)